Interactional norms in the Australian police interrogation room - Yoong, D. (SAGE Publications (UK and US), 2010)
The interaction that takes place in a police interrogation room follows certain conventions which are not evident in other settings like the school or home domains. This study which uses data derived from the questioning the Australian police conducted with Dr Mohamed Haneef - a terrorist accomplice suspect - aims to show how the norms of interaction in the Australian police interrogation room are established through protocols and codes of conduct. Another aspect of norms of interaction analysed in this article is the way power relations are created and maintained by looking at recurring discourse markers like the use of address and referent terms, interruptions, topic switching and latching. By identifying these linguistic devices, we are able to see the patterns of interaction conducted by the Australian police with persons of interest.